Transient Water Vapor at Europa's South Pole - Roth, Lorenz; Saur, Joachim; Retherford, Kurt D.; Strobel, Darrell F.; Feldman, Paul D.; McGrath, Melissa A.; Nimmo, Francis (AMER ASSOC ADVANCEMENT SCIENCE, 2014)
In November and December 2012, the Hubble Space Telescope (HST) imaged Europa's ultraviolet emissions in the search for vapor plume activity. We report statistically significant coincident surpluses of hydrogen Lyman-alpha and oxygen OI 130.4-nanometer emissions above the southern hemisphere in December 2012. These emissions were persistently found in the same area over the 7 hours of the observation, suggesting atmospheric inhomogeneity; they are consistent with two 200-km-high plumes of water vapor with line-of-sight column densities of about 10(20) per square meter. Nondetection in November 2012 and in previous HST images from 1999 suggests varying plume activity that might depend on changing surface stresses based on Europa's orbital phases. The plume was present when Europa was near apocenter and was not detected close to its pericenter, in agreement with tidal modeling predictions.